2022
DOI: 10.3847/1538-4357/ac6efd
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Large-scale Interplanetary Structures on the Propagation of Solar Energetic Particles: The Multispacecraft Event on 2021 October 9

Abstract: An intense solar energetic particle (SEP) event was observed on 2021 October 9 by multiple spacecraft distributed near the ecliptic plane at heliocentric radial distances R ≲ 1 au and within a narrow range of heliolongitudes. A stream interaction region (SIR), sequentially observed by Parker Solar Probe (PSP) at R = 0.76 au and 48° east from Earth (ϕ = E48°), STEREO-A (at R = 0.96 au, ϕ = E39°), Solar Orbiter (SolO; at R = 0.68 au, ϕ = E15°), BepiColombo (at R = 0.33 au, ϕ = W02°), and near-Earth spacecraft, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 83 publications
0
28
0
Order By: Relevance
“…Hardly any large SEP event of the STEREO era has escaped a detailed analysis by the SEP research community. Some notable examples are studies focusing on individual SEP proton events carried out by Wiedenbeck et al (2013) Most recently, the addition of SEP detectors on Parker Solar Probe (PSP) and Solar Orbiter (SolO) allowed multiplespacecraft analyses of solar cycle-25 SEP events (Cohen et al 2021;Kollhoff et al 2021;Lario et al 2022). The SEP spatial distributions are inferred from direct comparisons of SEP intensity profiles at different spacecraft.…”
Section: Longitudinal Distributions Of Sep Eventsmentioning
confidence: 99%
“…Hardly any large SEP event of the STEREO era has escaped a detailed analysis by the SEP research community. Some notable examples are studies focusing on individual SEP proton events carried out by Wiedenbeck et al (2013) Most recently, the addition of SEP detectors on Parker Solar Probe (PSP) and Solar Orbiter (SolO) allowed multiplespacecraft analyses of solar cycle-25 SEP events (Cohen et al 2021;Kollhoff et al 2021;Lario et al 2022). The SEP spatial distributions are inferred from direct comparisons of SEP intensity profiles at different spacecraft.…”
Section: Longitudinal Distributions Of Sep Eventsmentioning
confidence: 99%
“…The intensity-time profiles of the SEP event at SolO might be influenced by the arrival of a stream interaction region (SIR) during the SEP onset time. As discussed by Lario et al (2022), the high-speed stream driving the SIR was previously observed by STEREO-A and later also by near-Earth spacecraft, where it strongly affected the observed energetic ion intensity-time profiles. At SolO, the SIR and its associated magnetic compression might have acted as a magnetic mirror, reflecting some of the electrons back towards the inner heliosphere and the CMEdriven shock wave where the electrons may subsequently accelerate to higher energies.…”
Section: Phasementioning
confidence: 59%
“…We find that this is an interesting aspect of the event, hence, our analysis is focused on establishing an association between the energetic electrons and the different radio emissions during the impulsive phase of the flare and understanding the origin of the apparent second phase of electron energization after the flare maximum. Specifics on the energetic proton observations for this event can be found in Lario et al (2022).…”
Section: Introductionmentioning
confidence: 99%
“…In the left panels of Figure 9, we discern the region between the green vertical lines as the possible interval of the ICME by the below criteria: (1) lowered temperature, (2) continuously enhanced magnetic field strength, and (3) rotated magnetic field after October 13. Lario et al (2022) also use these signatures indicative of this ICME event. Throughout 2021 October 9-15, SolO did not record electron pitch angle, which brings uncertainty to the identification of the actual boundaries of the ICME.…”
Section: Evolution On the Ecliptic Planementioning
confidence: 99%
“…As the standoff distance between shock fronts and CME flux ropes increases from the nose to the flank, the long-duration sheath region can hint that the spacecraft likely observe the flank of CMEs (Chen et al 2022). (2) The relative location of the source region, SolO, and the L1 point, as shown by Lario et al (2022), implies that the left flank of the CME would arrive at SolO and the L1 point as a result of CME deflections caused by stream interaction regions (Liu et al 2019). The large differences between the observations at SolO and the L1 point could be explained by the radial and longitude separation at these two locations.…”
Section: Evolution On the Ecliptic Planementioning
confidence: 99%